2015
DOI: 10.3138/cmlr.2139
|View full text |Cite
|
Sign up to set email alerts
|

Le rôle de la prononciation dans l’intercompréhension entre locuteurs de français lingua franca

Abstract: L'objectif de cette étude était d'identifier les aspects de la prononciation en français qui ont mené à des problèmes de compréhension durant les interactions entre des locuteurs de français comme lingua franca. Neuf paires d'apprenants de français langue seconde inscrits à un cours de niveau intermédiaire ou avancé dans une université francophone au Québec ont accompli quatre tâches interactives en français, puis ont visionné les enregistrements de leurs échanges et commenté les problèmes de compréhension sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…And for L2 German, comprehensibility of L2 German speakers was predicted by phonetic, lexical, morphological, and fluency measures and by stress placement accuracy, but not by syntactic and phonological measures (O'Brien, 2014). The only relevant research to date comes from Kennedy, Guénette, Murphy, and Allard (2015) who recently showed that during task-based interactions between pairs of L2 French speakers, pronunciation accounted for 18% of the comprehension problems between the pairs (see also Bergeron & Trofimovich, 2017). The elements most frequently linked to comprehension problems were segments, particularly consonant production.…”
Section: L2 French Pronunciation Teachingmentioning
confidence: 99%
“…And for L2 German, comprehensibility of L2 German speakers was predicted by phonetic, lexical, morphological, and fluency measures and by stress placement accuracy, but not by syntactic and phonological measures (O'Brien, 2014). The only relevant research to date comes from Kennedy, Guénette, Murphy, and Allard (2015) who recently showed that during task-based interactions between pairs of L2 French speakers, pronunciation accounted for 18% of the comprehension problems between the pairs (see also Bergeron & Trofimovich, 2017). The elements most frequently linked to comprehension problems were segments, particularly consonant production.…”
Section: L2 French Pronunciation Teachingmentioning
confidence: 99%
“…Research demonstrates that the pronunciation of French segmentals is especially crucial for the ability of the learner to produce intelligible speech. For example, Kennedy et al (2015) found that mispronounced segments were a frequent cause of miscommunication among speakers of French as a lingua franca in Quebec. In this study, intermediate and high-level students participated in paired discussion tasks and then reviewed recordings of the activities to identify moments of confusion or miscommunication.…”
Section: The Importance Of Segmentalsmentioning
confidence: 99%
“…After vocabulary, pronunciation of segments was the second leading cause of communication difficulties among students. Frenchspecific suprasegmentals, such as liaison, were rarely used by the participants in Kennedy et al (2015) and therefore did not cause comprehension problems.…”
Section: The Importance Of Segmentalsmentioning
confidence: 99%